Analisis Penggunaan Wacana Persuasif Dalam Video Youtube Kampung Moderasi Beragama Desa Trubus, Bangka Tengah - Pricispa, Izcha (CV. ITTC INDONESIA, 2025)
This research will analyze persuasive discourse in YouTube videos of religious moderation in Trubus Village, Central Bangka using a qualitative approach with descriptive methods. This research examines persuasive techniques based on Keraf's theory and language style based on J.S. Badudu. The analysis shows that the constructed persuasive techniques include rationalization, conformity, identification, and suggestion. However, the most dominant persuasive technique constructed is the rationalization persuasive technique. These techniques have a significant role to then build collective representations related to religious moderation and interfaith tolerance. Furthermore, the use of polysyndeton and asyndeton language styles emphasizes the narrative structure and strengthens the message to be conveyed. Therefore, this YouTube video is not only an information medium but can be a discursive hegemony tool that will direct the audience's understanding of the importance of tolerance values in a multicultural society. Thus, this research will also confirm that, in the midst of current globalization, the media can be a medium for producing and reproducing discourses which can then affect the social reality of society.